The Value of T-SPOT.TB in Early Diagnosis of Tracheobronchial Tuberculosis - Han, Jiao; Zeng, Fanjun; Zhou, Yuanyuan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Objective: To evaluate the value of T-SPOT.TB in the diagnosis of tracheobronchial tuberculosis. Methods: This study included in January 2010 to October 2014 in the three gorges university during the first clinical medical college of final 283 diagnosed with tracheal bronchus TB patients (including 273 patients with pathological biopsy diagnosis and 10 called suspected TB patients), at the same time will be 283 active TB patients as a parallel control group included in this study. They were all given traditional detection methods acid fast stain and diseased tissue pathological biopsy and the new detection method T-SPOT.TB. Results: Sputum smear acid-fast stain sensitivity rate is 39.2% (111/283), typical TB diseased tissue pathology biopsy pathology morphology of 221 cases (78.1%), tend to TB 52 cases (18.4%),while T-SPOT. TB testing sensitivity and speciality rate is 93.6% (265/283) and 85.1% (241/283), which is much higher then the former two. Conclusion: T-SPOT.TB can provide important basis for the diagnosis of tracheobronchial tuberculosis.It is the fastest and most accu-rate method in the diagnosis of tracheobronchial tuberculosis. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32: 336-341)